Factors that Affect the Quality of Health Care Services in the North-West Province - Rakau, Mmule Evelyn (International Journal of Economics, Business and Management Studies, 2022)
The study was conducted to assess and evaluate the quality of health service delivery in the North-West Province of South Africa. Data was gathered by administering a questionnaire to 488 health professionals (public health administrators, medical doctors, pharmacists and professional nurses) working in various public health care facilities in the North-West Province. Results obtained from structural equations modelling (SEM) showed that the quality of health care services in designated health facilities in the North-West Province was influenced by 3 factors. These were the availability of enough number of suitably qualified health professionals at all designated health facilities, the ability to provide primary health care services to all people who need the services at all designated health facilities, and the availability of essential medicines and drugs at all times at all designated health facilities.